2023
DOI: 10.3390/jcm12103548
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Drug-Induced Myopathies Associated with the Combination of Statins and Daptomycin: A Disproportionality Analysis Using the US Food and Drug Administration Adverse Event Reporting System

Abstract: Background: Myopathy is one of the most common adverse reactions of daptomycin and statins. We aimed to evaluate the muscular toxicity of the combination therapy of daptomycin and statins in a large pharmacovigilance database. Methods: This was a retrospective disproportionality analysis based on real-world data. All cases reported between the first quarter of 2004 and the fourth quarter of 2022 where daptomycin and statins were reported were gathered from the US Food and Drug Administration Adverse Event Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Secondly, causality could not be inferred or determined because patient treatment information is often incomplete, including patient history and reported duration of drug use. We were unable to identify any other factors that might have influenced the results (Wei et al, 2023a). Finally, our study was unable to describe the mechanism behind the increased adverse effects.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Secondly, causality could not be inferred or determined because patient treatment information is often incomplete, including patient history and reported duration of drug use. We were unable to identify any other factors that might have influenced the results (Wei et al, 2023a). Finally, our study was unable to describe the mechanism behind the increased adverse effects.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, our study showed that two or more statins history group exhibited stronger signals than the single-agent regimen. However, it was worth noting that the utilization of multiple statins in clinical practice was uncommon and typically limited to patients requiring a switch in statin therapy due to intolerance (Wei et al, 2023a). Due to the unavailability of information regarding concurrent or sequential use of multiple statins in the FAERS database, a comprehensive analysis and discussion of the data cannot be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…We collected the reports in the FAERS database from the first quarter of 2004 (inception of the database) to the fourth quarter of 2022. The data sources of the FAERS are public and self-reported for post-marketing drug safety monitoring ( Wei et al, 2023 ). ADRs were reported with anonymous patient information.…”
Section: Methodsmentioning
confidence: 99%
“…The FAERS database references the standardization and classification of ADRs in the Medical Dictionary for Regulatory Activities (MedDRA) ( Wei et al, 2023 ). Each report is coded by preferred terms (PTs) from the MedDRA terminology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation